Pilot modelling for airframe loads analysis - Lone, Mudassir M. (Cranfield University, 2013)
The development of large lightweight airframes has resulted in what used to be high frequency structural dynamics entering the low frequency range associated with an aircraft’s rigid body dynamics. This has led to the potential of adverse interactions between the aeroelastic effects and flight control, especially unwanted when incidents involving failures or extreme atmospheric disturbances occur. Moreover, the pilot’s response in such circumstances may not be reproducible in simulators and unique to the incident. The research described in this thesis describes the development of a pilot model suitable for the investigation of the effects of aeroelasticity on manual control and the study of the resulting airframe loads. After a review of the state-ofthe- art in pilot modelling an experimental approach involving desktop based pilot-in-the-loop simulation was adopted together with an optimal control based control-theoretic pilot model. The experiments allowed the investigation of manual control with a nonlinear flight control system and the derivation of parameter bounds for single-input-single-output pilot models. It was found that pilots could introduce variations of around 15 dB at the resonant frequency of the open loop pilot-vehicle-system. Sensory models suitable for the simulation of spatial disorientation effects were developed together with biomechanical models necessary to capture biodynamic feedthrough effects. A detailed derivation and method for the application of the modified optimal control pilot model, used to generate pilot control action, has also been shown in the contexts of pilot-model-in-the-loop simulations of scenarios involving an aileron failure and a gust encounter. It was found that manual control action particularly exacerbated horizontal tailplane internal loads relative to the limit loads envelope. Although comparisons with digital flight data recordings of an actual gust encounter showed a satisfactory reproduction and highlighted the adverse affects of fuselage flexibility on manual control, it also pointed towards the need for more incident data to validate such simulations.
Keywords: Pilot modelling; manual control; pilot-model-in-the-loop simulation; flight loads; aeroelastics; flight control